Cigarette, Waterpipe, and Electronic Cigarette Use Among College Fraternity and Sorority Members and Athletes in the United States - Soule, Eric K. (J Am Coll Health, 2019)
OBJECTIVE: To examine the association between fraternity/sorority membership and athlete status with tobacco use by tobacco product type. PARTICIPANTS: Undergraduate college students who participated in the Spring 2017 National College Health Assessment-II Survey (n=47,821). METHODS: Prevalence of current (past-30 day) cigarette smoking, waterpipe tobacco smoking (WTS), and e-cigarette (ECIG) use was examined. Logistic regressions examined associations between fraternity/sorority membership and participation in collegiate athletics with tobacco use. RESULTS: Fraternity/sorority members had the highest current use rates for cigarettes, waterpipe tobacco, and ECIGs and were nearly twice as likely to report cigarette smoking, WTS, and ECIG use relative to non-fraternity/sorority members. Relative to non-varsity athletes, varsity athletes were less likely to report cigarette smoking and WTS, but not ECIG use. CONCLUSIONS: Fraternity/sorority members appear to be at risk for use of multiple tobacco products. Varsity athlete status may be protective for some tobacco products, but does not appear no for ECIG use. ECIGs may appeal to groups typically at low risk for other tobacco products.